Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1038/ejcn.2010.122
|View full text |Cite
|
Sign up to set email alerts
|

Effects of margarines and butter consumption on lipid profiles, inflammation markers and lipid transfer to HDL particles in free-living subjects with the metabolic syndrome

Abstract: Objective: Our purpose was to examine the effects of daily servings of butter, no-trans-fat margarine and plant sterol margarine, within recommended amounts, on plasma lipids, apolipoproteins (Apos), biomarkers of inflammation and endothelial dysfunction, and on the transfer of lipids to HDL particles in free-living subjects with the metabolic syndrome. Methods: This was a randomized, single-blind study where 53 metabolic syndrome subjects (62% women, mean age 54 years) received isocaloric servings of butter, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 41 publications
2
14
0
5
Order By: Relevance
“…On the contrary, the other four of these studies [17, 19, 20, 23] reported no changes in CRP values. This discrepancy could be due to the nature of the botanicals used, the bioavailability of active compounds, the number of patients enrolled in the study, the type of study, and/or the laboratory methods for biomarker measurement.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…On the contrary, the other four of these studies [17, 19, 20, 23] reported no changes in CRP values. This discrepancy could be due to the nature of the botanicals used, the bioavailability of active compounds, the number of patients enrolled in the study, the type of study, and/or the laboratory methods for biomarker measurement.…”
Section: Resultsmentioning
confidence: 89%
“…E-selectin levels were evaluated in four studies [1719, 23], but a decrease was recorded in only one [18], which rules out this biomarker as suitable for the purpose. TNF- α levels were evaluated in three studies [16, 18, 19], and two of them [16, 18] reported a significant reduction after treatment with soy proteins (8 weeks) and fresh algae infusion (10 weeks).…”
Section: Resultsmentioning
confidence: 99%
“…Fora da fase micelar, o colesterol não é mais solúvel, formando cocristais com fitosteróis, sendo, então, excretado juntamente com os fitosteróis não absorvidos 129 . Com isso, observam-se efeitos na diminuição do colesterol, especialmente LDL-c, ocasionados por fitosteróis 130 . O consumo diário de dois gramas de fitosteróis sob a forma de margarinas enriquecidas reduz a absorção de colesterol em aproximadamente 30% 40%, o que ocasiona uma redução média no LDL-c de 8,8% 131 .…”
Section: Fitosterolunclassified
“…De plus, chez des sujets en surpoids ou obèses, des régimes alimentaires supplémentés en matière grasse laitière (≈ 50 g sur les 72 g de matière grasse consommée pendant 4 semaines) apportée soit sous forme de produits laitiers fermentés (fromage et yaourt) soit non fermentés (beurre, crème et crème glacée), n'induisent pas de différences en basal des concentrations plasmatiques de MCP-1, IL-6, IL-1␤, TNF-␣ et CRP ultrasensible [77]. Chez des sujets présentant un syndrome métabolique, une supplémentation en matière grasse tartinée (beurre vs margarine sans AG trans vs margarine aux stérols végétaux) à raison de 12 g de MG supplémentaire par jour, n'a aucun impact sur les marqueurs plasmatiques de l'inflammation (entres autres, CRP et IL-6) à jeun, après 5 semaines d'intervention, et ce quelle que soit la MG testée [78]. Par ailleurs, une étude épidémiologique menée sur des adolescents sains normo-pondérés ou en surpoids a mis en évidence que ceux ayant des taux plasmatiques élevés en acides gras C15:0 et C17:0 (marqueurs de la consommation de matière grasse laitière) présentaient les plus faibles taux d'IL-6 plasmatiques, quel que soit leur IMC [79].…”
Section: Modulation De L'inflammation Et De L'endotoxémie Par La Matiunclassified